2008
DOI: 10.1080/15287390802271723
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Porphyrinuria in Australian Children with Autism

Abstract: Two recent studies, from France (Nataf et al., 2006) and the United States (Geier & Geier, 2007), identified atypical urinary porphyrin profiles in children with an autism spectrum disorder (ASD). These profiles serve as an indirect measure of environmental toxicity generally, and mercury (Hg) toxicity specifically, with the latter being a variable proposed as a causal mechanism of ASD (Bernard et al., 2001; Mutter et al., 2005). To examine whether this phenomenon occurred in a sample of Australian children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 17 publications
5
22
0
Order By: Relevance
“…Nataf et al (2006) found that children with autism have higher levels of precoproporphyrin, a biomarker for Hg toxicity, than neurotypical children. This finding was confirmed by Geier and Geier (2007) and Geier et al (2009) in the United States, Austin and Shandley (2008) in Australia, and Youn et al (2010) in Korea. Thimerosal-containing hepatitis B shots were associated with delayed acquisitions of vital reflexes in baby macaques (Hewitson et al 2010).…”
supporting
confidence: 73%
“…Nataf et al (2006) found that children with autism have higher levels of precoproporphyrin, a biomarker for Hg toxicity, than neurotypical children. This finding was confirmed by Geier and Geier (2007) and Geier et al (2009) in the United States, Austin and Shandley (2008) in Australia, and Youn et al (2010) in Korea. Thimerosal-containing hepatitis B shots were associated with delayed acquisitions of vital reflexes in baby macaques (Hewitson et al 2010).…”
supporting
confidence: 73%
“…This type of phenomena is particularly evident when comparing the relative 5-10% increase in the Hg-associated porphyrins observed in our study with other studies linking elevated Hg-associated porphyrins with diagnosed Hg-related neurological disorders. For example, several recent studies revealed twofold to threefold significantly higher Hg-associated porphyrins among children diagnosed with neurodevelopmental disorders in comparison to neurotypical children Geier 2006, 2007;Geier et al 2009a, b;Nataf et al 2006;Austin and Shandley 2008;Young et al 2010;Kern et al 2010a, b).…”
Section: Discussionmentioning
confidence: 93%
“…These investigators observed that urinary porphyrins were as sensitive as urinary Hg levels for predicting adverse effects of Hg on cognitive and motor testing. Several studies have been completed recently that used urinary porphyrins to examine Hg toxicity in children, both in neurotypical children and in children with neurodevelopmental disorders Geier 2006, 2007;Kern et al 2010b;Nataf et al 2006;Austin and Shandley, 2008;Young et al 2010). Several of these studies examined the relationship between the severity of the neurological impairment and urinary porphyrins, and found significant positive correlations with Hg-associated urinary porphyrins and the severity of the neurological impairment (Nataf et al 2006;Geier et al 2009a, b;Kern et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrins are a necessary intermediate in heme production, and metals such as mercury have been shown to inhibit the enzymes uroporphyrin decarboxylase and coproporphyrinogen oxidase, causing an excessive urinary porphyrin excretion. Porphyrinuria is not only a biomarker of Hg damage but also a concomitant biological occurrence in ASD (Austin and Shandley 2008;Garrecht and Austin 2011). In addition, children with increasingly severe ASD measured by CARS scores correlated with increasing levels of urinary porphyrins associated with Hg body burden (Geier et al 2009a, b).…”
Section: Mercury and Asdsmentioning
confidence: 99%
“…Recent investigations identified atypical urinary porphyrin profiles in children with autism (Nataf et al 2006;Geier and Geier 2007a;Austin and Shandley 2008). Porphyrins are a necessary intermediate in heme production, and metals such as mercury have been shown to inhibit the enzymes uroporphyrin decarboxylase and coproporphyrinogen oxidase, causing an excessive urinary porphyrin excretion.…”
Section: Mercury and Asdsmentioning
confidence: 99%